2019
DOI: 10.1111/jav.01766
|View full text |Cite
|
Sign up to set email alerts
|

Flexible response to short‐term weather in a cold‐adapted songbird

Abstract: To improve survival during winter, temperate species use a variety of behavioural and physiological adaptations. Among songbirds, the maintenance of lipid reserves is a widely‐used strategy to cope with the severity of winter; however, little is known regarding how multiple synchronously acting environmental mechanisms work together to drive these effects. In a context where temperate winter conditions are becoming more variable, it is important to widen our understanding regarding the flexible adaptations tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…The long-term banding data analyses revealed maximum temperatures and snow depth were the most important weather variables correlated with changes in flock composition by sex and size. These results are consistent with our earlier study showing that these variables were also central in informing daily fattening patterns in Snow Buntings (Laplante et al, 2019). Snow depth may rank foremost, considering that snow buntings are granivorous ground-feeders which can have more difficulty accessing resources in areas of high snow depth, and record-high numbers of Snow Buntings have been observed during warmer (less snowy) winters in Central Europe (Orlowski and Gebski, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The long-term banding data analyses revealed maximum temperatures and snow depth were the most important weather variables correlated with changes in flock composition by sex and size. These results are consistent with our earlier study showing that these variables were also central in informing daily fattening patterns in Snow Buntings (Laplante et al, 2019). Snow depth may rank foremost, considering that snow buntings are granivorous ground-feeders which can have more difficulty accessing resources in areas of high snow depth, and record-high numbers of Snow Buntings have been observed during warmer (less snowy) winters in Central Europe (Orlowski and Gebski, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Movements may also be influenced by male dominance over food resources, where females may be forced to move away when weather is severe because they are simply unable to access food and accumulate the required fat store to survive cold nights. Laplante et al (2019) reported that for their body size, females were carrying more fat than males. In Snow Buntings wintering in Scotland, females were more likely to move when flock sizes were larger, presumably because they were excluded by dominant individuals when intraspecific competition increased (Smith and Metcalfe, 1997a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations